2014
DOI: 10.1002/pen.23941
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of silica nanoparticles and exfoliated graphite nanoplatelets on the crystallization behavior of isotactic polypropylene

Abstract: This study explores how the presence of nanofillers with different structural and chemical characteristics, specifically silica nanoparticles and exfoliated graphite nanoplatelets (GNP), alters the crystallization behavior and polymorphism of a semicrystalline polymer, such as polypropylene (PP). The main focus of this research is to investigate how silica and GNP affect the nucleation and growth of PP crystals during isothermal crystallization. The nonisothermal crystallization behavior, including crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Previous works showed no obvious change in the crystallinity of PP/GnPs composites using very low quantity of GnPs [9,10,13,14,22] or for its similar platelet form filler, clay, in PP/clay nanocomposite fibres, even if the some compatibilizers was used [19,[41][42][43][44]. To our best knowledge, our DSC results have, for the first time, shown the flow-induced crystallization for PP/GnPs nanocomposite systems.…”
Section: Flow-induced Crystallizationmentioning
confidence: 45%
See 1 more Smart Citation
“…Previous works showed no obvious change in the crystallinity of PP/GnPs composites using very low quantity of GnPs [9,10,13,14,22] or for its similar platelet form filler, clay, in PP/clay nanocomposite fibres, even if the some compatibilizers was used [19,[41][42][43][44]. To our best knowledge, our DSC results have, for the first time, shown the flow-induced crystallization for PP/GnPs nanocomposite systems.…”
Section: Flow-induced Crystallizationmentioning
confidence: 45%
“…During the last decade, PP/graphene nanocomposites were studied extensively [2,[9][10][11][12][13][14][15][16]. These researches showed that the properties of nanocomposites, such as mechanical properties, are dependent on the state of dispersion of graphene in the matrix and loading amount of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…At low loadings especially, the increase is quite intense as with just 0.2 wt.% of filler the crystallization temperature increases by 7 °C in comparison with the value observed for the pure polymer (113.6 °C to 120.8 °C). This behavior can be associated with nucleation effects and has been reported in the past for a number of fillers including clay, nanotubes and graphitic platelets [35,61,62]. Polypropylene has a very rich polymorphism form and it has been reported that filler inclusion has an effect of the overall morphology of the system [56].…”
Section: Morphologymentioning
confidence: 64%
“…The increase in resistance under impact conditions exhibited by the hybrid composites at low filler loadings can be ascribed to (i) changes in the energy absorbing mechanisms (i.e., higher plastic deformation of the matrix along the filler/matrix interface, crack branching due to hindrance by reinforcements, bridging of the crack, creation of voids etc.) and (ii) different crystalline morphology (i.e., spherulite size and polymorphism) occurring upon nanomodification . However, the toughening effect provided by high modulus filler particles ( E ∼70 GPa for GNP) is limited by nanofiller agglomeration.…”
Section: Resultsmentioning
confidence: 99%